Polymer Matrix and Manufacturing Methods in Solid Dispersion System for Enhancing Andrographolide Solubility and Absorption: A Systematic Review - Pratchaya Tipduangta; Sunee Chansakaow; Pimpimon Tansakul; Rungarun Meungjai; Piyameth Dilokthornsakul (MDPI AG, 2024)
Background: Andrographolide (ADG) has poor aqueous solubility and low bioavailability. This study systematically reviews the use of solid dispersion (SD) techniques to enhance the solubility and absorption of ADG, with a focus on the methods and polymers utilized. Methodology: We searched electronic databases including PubMed, Web of Science, Scopus®, Embase and ScienceDirect Elsevier® up to November 2023 for studies on the solubility or absorption of ADG in SD formulations. Two reviewers independently reviewed the retrieved articles and extracted data using a standardized form and synthesized the data qualitatively. Results: SD significantly improved ADG solubility with up to a 4.7-fold increase and resulted in a decrease in 50% release time (T1/2) to less than 5 min. SD could also improve ADG absorption, as evidenced by higher Cmax and AUC and reduced Tmax. Notably, Soluplus-based SDs showed marked solubility and absorption enhancements. Among the five SD techniques (rotary evaporation, spray drying, hot-melt extrusion, freeze drying and vacuum drying) examined, spray drying emerged as the most effective, enabling a one-step process without the need for post-milling. Conclusions: SD techniques, particularly using Soluplus and spray drying, effectively enhance the solubility and absorption of ADG. This insight is vital for the future development of ADG-SD matrices.